Responsibility for user-generated content in the collaborative Internet - Franganillo, Jorge (Anuario ThinkEPI, 2009)
The ease with which any contribution can be published on the collaborative Web favours the spreading of inappropriate or offensive content, posted with anonymity. User-generated material in forums and other participatory spaces must be moderated, without confusing control with censorship. The lack of control over content causes harmful consequences and it´s not a technical limitation, but a negligence that can be penalized by law, in spite of some legal vacuum.
Keywords: Web 2.0; User-generated content; Freedom of speech; Best practices; Law.